Usability Evaluation of a 3D Digital-TwinIndirect usability evaluation of SOMA – System Oriented to Monitoring of Engineering Assets - Tiecher Sefrin, Yuri Fernando; Mauricio, Claudio Roberto Marquetto; Peres, Fabiana Frata Furlan (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2021: Anais do XXIII Simpósio de Realidade Virtual e Aumentada, 2021)
The evaluation of software usability is a very important topic for society. Usability depends on factors intrinsic to the task to be performed. In hydroelectric plants, the main task to be performed by operators is the analysis and monitoring of the sensors of the generating unit. The hypothesis is that the use of a 3D interface brings more usability and efficiency to find the sensors. The work applies Nielsen’s heuristics to ensure good usability. This work intends to evaluate the usability of SOMA – System Oriented to Monitoring of Engineering Assets, a software that monitor Hydroelectric Power Plant, operation of electricity generation plants, in terms of increasing availability and reducing maintenance costs. The results of this indirect usability evaluation were positive, suggesting new features to the software to help engineers to perform even better their tasks on monitoring assets.